Mites on Annonaceae species in northeast Brazil and in the state of Para - Sousa, Josilene Maria de; Gondim, Manoel Guedes Corrêa; Lofego, Antonio Carlos [UNESP]; Moraes, Gilberto José de (Acarologia-Universite Paul Valery, 2015)
The family Annonaceae Juss. comprises over 120 genera and 2000 species with origins in the American, Asian and African tropical regions. Many of these species, such as those of the genera Annona, Rollinia, Duguetia, Uvaria and Asimira, are edible. Some pests have been reported in soursop, sugar apple and atemoya, the main annonas grown in Brazil. However, few mites are mentioned as pests of this plant family. This study aimed to identify mite species. associated with the Annonaceae in northeastern Brazil and in the state of Para. A survey was conducted, collecting samples of Annona muricata L. (soursop), Annona squamosa L. (sugar apples), Annona cherimola x A. squamosa (atemoya) and Annona coriacea Mart. (araticum) leaves. Annona coriacea is a wild Annonaceae widely distributed in northeastern Brazil. For each sample, a total of 100 leaves were collected from five individuals of the same species at each site. The samples were taken to the laboratory, where they were processed and the mites were mounted and identified. The mite species found belonged to the families Ascidae, Bdellidae, Phytoseiidae, Stigmaeidae, Tarsonemidae, Tetranychidae, Tenuipalpidae and Tydeidae. Phytoseiidae, Tetranychidae and Tydeidae had the highest diversity. Five of the reported species were found on all four of the studied cultures: Amblyseius aerialis (Muma), Tetranychus mexicanus (McGregor), Parapronematus acaciae Baker, Pronematus ubiquitus (McGregor) and Agistemus floridanus Gonzales.
Keywords: Acari; Diversity; Mites; Annona muricata; Annona squamosa